Using Tools to Regulate the Transition to a Green Economy and Preserve the Environment for Countries Exporting Raw Materials - TATIBEKOVA, Aida; ALTAY, Marat; KURALBAEV, Almas; MARKHAYEVA, Bayanslu A.; KARSHALOVA, Alma (Journal of Environmental Management and Tourism, 2022)
This article considers the tools that form the organizational and financial basis for the green economy transition and the features of their application. Currently, most countries of the world have taken a course towards the green economy transition to ensure a decent life for society while preserving the environment. The study aims at seeking the most effective tools for managing such a transition in a certain order and on time. The article dwells on the state regulation of environmentally oriented industries and support for green investments, as well as social orientation towards the environment. A special emphasis is laid on market-based instruments for financing the development of the green economy, including green bonds. The authors of the article have presented a model of transition to green growth with minimum losses for commodity-exporting countries using special financial instruments that ensure the green economy transition for enterprises in the fuel and energy complex. They also have formed proposals for improving the regulatory potential of environmental legislation and the main objects influenced by the state environmental policy.